STRATEGI KOPING SISWA PENGHAFAL AL-QUR’AN DAN INTERVENSI GURU DALAM OPTIMALISASI WAKTU SETORAN ZIYADAH DAN MUROJA’AH DI TENGAH KETERBATASAN WAKTU SEKOLAH VOKASI SMKN 1 PURWOSARI - Yusnia Ulul Azmi; Askhabul Kirom (STKIP Subang, 2026)
The integration of the Quran memorization program into Vocational High Schools (SMK) faces complex challenges due to time constraints caused by demanding academic and practical schedules. This condition triggers physical and psychological stress, leading to inconsistent memorization (ziyadah and muroja'ah) deposit frequencies. This study aims to describe the coping strategies used by tahfidz students, the forms of teacher interventions in optimizing deposit time, and the inhibiting factors at SMKN 1 Purwosari. This study applied a qualitative approach with a case study design. Data were collected through direct observation, in-depth interviews with 1 tahfidz teacher and 5 student trainees, and documentation review. Data analysis followed the interactive model of Miles and Huberman (data reduction, data display, and conclusion drawing). Findings revealed that: (1) Students' coping strategies included problem-focused coping (utilizing micro-times during school breaks/free periods) and emotion-focused/religious coping (calming stress through prayer, dhikr, and spiritual mindset); (2) Teacher interventions were implemented through a flexible